Identifying integration types for requirement analysis in CIM development - Hashemipour, Majid; Kayaligil, Sinan (My University, 1999)
This paper presents the second phase of a computer- assisted methodology for requirement and design analysis stages of implementing CIM within small and medium-size enterprises (SME). The main objective is to cover informational and functional analysis during the CIM system life-cycle. The methodology aims at using limited expertise, limited staff, and expenditure, making it especially suited for introducing CIM in SMEs. The paper emphasises the integration aspects of the methodology as the key factors in the requirement and design analysis stages of the implementation of CIM. Integration has been taken as the need to have some form of operational collaboration between two or more functions. Four types of integration have been identified for reducing the complexity of data communications and for narrowing the gap between analysis and implementation phases. A computer-supported information requirement analysis tool has been developed for implementing the methodology. A case study was carried out in the apparel industry to test the methodology. © 1999, MCB UP Limited
Keywords: Clothing industry; Computer-integrated manufacturing; Integration; Small to medium-sized enterprises